The Results of a Study on Teachers’ Problems and Needs Regarding the Organization of Learning Activities in the Earth and Space Science Course at the Grade 10 Level - Pinasa, Siwa (Journal of Teacher Professional Learning Community (JTPLC) (Online), 2025)
This study aimed to explore the problems, obstacles, and needs of teachers regarding the organization of learning activities in Earth and Space Science. Data were collected from ten Earth and Space Science teachers with at least ten years of teaching experience. The research instruments included semi-structured interviews and records from Professional Learning Community (PLC) meetings. The PLC meeting records were compiled and analyzed using content analysis, involving coding and categorization procedures. The qualitative data analysis revealed five major categories of problems in the teaching and learning of Earth and Space Science: (1) issues related to highly abstract content and a lack of connections to empirical evidence; (2) issues related to instructional processes that emphasize lecture-based teaching with limited opportunities for hands-on learning; (3) issues related to students’ skills and attitudes toward astronomy; (4) issues related to insufficient or inappropriate instructional media, activities, and learning innovations; and (5) issues related to assessment and evaluation practices that fail to reflect students’ scientific competencies. The most frequently reported problems were lecture-centered instructional approaches and the lack of instructional media or activity sets that promote hands-on learning (100%), followed by abstract content (90%) and students’ skills and attitudes (80%).The findings are consistent with related research, highlighting the necessity of shifting instructional practices toward inquiry-based learning and the use of authentic data. The researcher therefore recommends the development of Earth and Space Science laboratory activity sets based on Activity-Based Learning (ABL) with a scaffolding structure to reduce students’ learning difficulties, integrate authentic empirical data into learning activities, and design assessment methods aligned with scientific competencies.